Effect of olive husk flour silanization on the mechanical and thermal properties of high-density polyethylene composites - IHAMOUCHEN, Chadia (Biopolymer Applications Journal, 2025)
The present paper summarizes an experimental study on the mechanical and thermal behavior of olive husk flour (OHF) reinforced high-density polyethylene (HDPE) composites. Several formulations of PE filled with 10, 20 and 30 % by weight of untreated olive husk and that treated with vinyltriacetoxy-silane (VTAS) were prepared. Fourier transform infrared (FTIR) spectroscopy was used to analyse involved silanization reactions. Scanning electron microscopy (SEM) was used to show the morphology of the flour surface. Furthermore, the mechanical and thermal characteristics of the various composite samples were investigated as a function of both loading contents and chemical treatment. The results showed that the properties of the composite materials are positively affected by silanization treatment of OHF.